Produção de melão no semiárido brasileiro: fator de emissão de óxido nitroso (n20) e qualidade pós-colheita - Silva, Laiane Torres (Universidade Federal Rural do Semi-Árido, 2015)
Brazil is one of the top global producers of melon, especially the states of Ceará and Rio Grande do Norte. Obtaining high productivity and fruit quality depends on factors such as the use of fertilizers and the cultivation system. Fertilizer use aims to meet the nutritional needs of the plant, with the adverse effect, the increase in emissions of nitrous oxide, a potent greenhouse gas, requiring its monitoring in order to optimize its use.In turn, cultivation systems that make use of vegetable cover crops have been an alternative for providing benefits to the soil system, reduce the use of water and allowing obtain fruits with good quality. Emissions of nitrous oxide were quantified and its emission factor was determinated, from a proposed method involving gas collects at different points, during the cycle of the yellow melon "Goldex", at the production center Ceará / Rio Grande do Norte. For the collections, static cameras were positioned on mulching, as well as at the side and center of the lines, being emissions quantified by gas chromatography, using the electron capture detector.The postharvest quality was evaluated for fruits produced in two seasons (2011 and 2012), using green manure and tillage with different cover crops. External appearance, weight loss, firmness, soluble solids and total sugars were analyzed at the beginning and end of storage, which consisted of 22 days at 11 ° C and 85-90% RH over six days at 20 ° C and 85 to 90% RH. The overall emissions and emission factor for N2O (0.15%) were low in relation to other cultures, suggesting that the dynamics of gas emission into the melon crop was low throughout the cycle.There were no significant changes to the appearance of fruits, firmness and weight loss. Soluble solids and total sugars were better preserved in fruits from the system with green manure, and the highest levels found in green manure using sun hemp and millet more sun hemp, associated with plastic mulching. The combined use of green manure with these two cover crops can be an alternative in the production of melons "Goldex" with good commercial quality and greater preservation of natural resources in melon production center in the states of Ceará and Rio Grande do Norte
Keywords: Cucumis melo L.; Fertilizante nitrogenado; Fator de emissão; Sistemas de cultivo; Qualidade dos frutos; Cucumis melo L.; Nitrogen fertilizer; Emission factor; Cultivation systems; Fruit quality; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA